KETERAMPILAN BERPIKIR KREATIF SISWA DALAM MENYELESAIKAN SOAL OLIMPIADE MATEMATIKA BERDASARKAN LEVEL METAKOGNISI - Mohammad Tohir (Fakultas Tarbiyah Universitas Ibrahimy, 2019)
The research aims to describe the level of creative thinking ability of students in solving mathematics olympiad problems based on students' metacognition levels by using the qualitative descriptive approach. The subjects of this study were the students at State of Junior High School (SMPN) 2 Jember involving the learning of Olympiad mathematics. The data collection was carried out based on the student's creative thinking ability test sheets, interviews, and observations. Test questions given to the students were mathematics olympiad questions. The analysis of the Miles and Huberman models were used for data analysis. The results exhibited that the level of creative thinking skills of the students in solving mathematics Olympiad questions were 29.41% (less creative), 41.18% (quite creative), 11.76% (creative) and 17.65% (very creative). On the other hand, the metacognitive level of SMPN 2 Jember students were 64.71% at level 2 (aware use), 23.53% at level 3 (strategic use) and 11.76% at level 4 (reflective use). In addition, the literatures indicate that there are several factors affectting the creative thinking skills and metacognition level, among them is an understanding of the information of the problem, compiling an appropriate strategies, skills of the chosen strategy, skills of answer elaboration, mastery of the Mathematics Olympiad material and a tendency to rely on the memorization or imitations based on previous or discussed solutions.